Kinematics of a 2D Asymmetric Nonlinear Oscillator - Sarafian Haiduke (Scientific research, 2014)
Motion of a point-like massive particle under the influence of two nonidentical linear springs conducive to an irregular planar oscillation is analyzed. For a two dimensional oscillations the equation of motion is a coupled highly nonlinear differential equation. The set of equations cannot be solved analytically. Utilizing a Computer Algebra System (CAS) such as Mathematica [1] we solve the equations numerically. Kinematics of the particle is presented. For a comprehensive visual understanding the oscillations are simulated. We also include an extended atlas of useful two-dimensional time-folded diagrams
Keywords: 2D Nonlinear Oscillator; Computer Algebra System; Mathematica